The variables in the research method of the Sociology of Law (Società e diritti, 2018)
The method of scientific research has in the variable a fundamental concept for its development. In this sense, research in the Sociology of Law, makes it necessary to understand the concept of variable and its typology. Below is a brief review of these aspects. A typology of "cumulative" variables is proposed.Key words: Sociologyof Law, Empirical research, Cumulative variables